2016
DOI: 10.1016/j.crci.2016.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Light-driven electron transfer in a modular assembly of a ruthenium(II) polypyridine sensitiser and a manganese(II) terpyridine unit separated by a redox active linkage. DFT analysis

Abstract: A series of ruthenium polypyridine-based complexes covalently bound to a terpyridine coordinating site for Mn II ion coordination has been developed. A redox active unit separates the photoactive unit and the manganese complex. Introducing ester groups on the bipyridine skeleton allows modulation of redox properties of the chromophore. Intramolecular electron transfer from the Mn II to the photogenerated Ru III was studied by timeresolved transient absorption and EPR. Photophysical studies support the particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
0
4
1
Order By: Relevance
“…We have pursued our effort to unravel the implication of a molecular electron relay in photosensitizer-redox-active-manganese complexes. In a previous study, we found that decorating the bipyridine ligands with ester functions acting as electron-withdrawing groups and inducing an anodic shift by ca.160 mV of the Ru III/II redox couple led to the distinction of the imidazole redox activity in contrast with our previous models [18]. However, its participation in the oxidation of the Mn(II) center could not be established.…”
Section: Introductioncontrasting
confidence: 65%
See 4 more Smart Citations
“…We have pursued our effort to unravel the implication of a molecular electron relay in photosensitizer-redox-active-manganese complexes. In a previous study, we found that decorating the bipyridine ligands with ester functions acting as electron-withdrawing groups and inducing an anodic shift by ca.160 mV of the Ru III/II redox couple led to the distinction of the imidazole redox activity in contrast with our previous models [18]. However, its participation in the oxidation of the Mn(II) center could not be established.…”
Section: Introductioncontrasting
confidence: 65%
“…The presence of the divalent ion in the terpyridine also affects this band implicating a certain degree of interaction. Mirroring the red-shift observed on the electronic absorption spectra, the emission maximum for the complexes occurs at 645-650 nm instead of 610 nm (Table S1) [18]. Compared to Ru(bpy) 3 , the emission lifetime is increased from 0.8 to 1-1.6 µs (Fig.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations